HGA-2, a novel galactoside-binding lectin from the sea cucumber Holothuria grisea binds to bacterial cells - Melo, Arthur Alves de (2014)
A novel lectin, HGA-2, was isolated from the sea cucumber Holothuria grisea. The protein was isolated by a single chromatographic step using a column of Guar Gum as affinity. HGA-2 showed an apparent molecular mass of 17 kDa and 34 kDa under reducing and nonreducing conditions, respectively. The hemagglutinating activity was specific for rabbit erythrocytes, showing no activity for human blood A, B and O. Its hemagglutinating activity was inhibited by carbohydrates containing galactose, with higher affinity for GalNAc and glycoprotein porcine stomach mucin (PSM). HGA-2 was stable at pH 6–10, significantly declining at pH 5 and a temperature of 40 °C, with its activity being abolished at 100 °C. The HGA-2 protein was found to be Ca2+-dependent; it was highly toxic against Artemia nauplii and able to recognize and agglutinate cells of Escherichia coli. Amino acid sequences of tryptic peptides of HGA-2 strongly suggest that HGA-2 is a member of the C-type lectin family.